Pengaruh Kualitas Produk, Citra Merek dan Promosi Terhadap Kepuasan Pelanggan Pada Produk Maybelline di Kota Batam - Natania Natania; Triana Ananda Rustam (eCo-Buss, 2023)
Maybelline is a various splendor product with pleasant that is not inferior to nearby merchandise, however, Maybelline ought to be able to compete with nearby manufacturers thinking about that presently there are many Indonesian humans, in particular ladies who honestly like nearby products, that is due to the fact neighborhood merchandise are able to offer great merchandise. the excellent, as well as a logo image that is easy to don't forget and a very appealing promoting, consequently it substantially influences patron pleasure. As for the motive of this examine to discover how product first-class, logo photo and promoting can have an effect on patron pleasure with Maybelline merchandise in Batam town. This studies combines quantitative and descriptive techniques. The population used consists of buyers or consumers of Maybelline merchandise in Batam town which might be determined with the aid of the Jacob Cohen method and 204 responses. The analytical contraptions encompass statistical descriptive exams, facts first-class assessments, classical assumption exams, affect exams, and speculation trying out. The findings of this take a look at imply that product pleasant, brand image, and promoting have a fine and statistically enormous impact on customer pride with Maybelline merchandise in Batam metropolis